2004
DOI: 10.1152/ajpheart.00678.2002
|View full text |Cite
|
Sign up to set email alerts
|

CO modulates pulmonary vascular response to acute hypoxia: relation to endothelin

Abstract: Pulmonary intralobar arteries express heme oxygenase (HO)-1 and -2 and release carbon monoxide (CO) during incubation in Krebs buffer. Acute hypoxia elicits isometric tension development (0.77 +/- 0.06 mN/mm) in pulmonary vascular rings treated with 15 micromol/l chromium mesoporphyrin (CrMP), an inhibitor of HO-dependent CO synthesis, but has no effect in untreated vessels. Acute hypoxia also induces contraction of pulmonary vessels taken from rats injected with HO-2 antisense oligodeoxynucleotides (ODN), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The salutary effect of the enhancement of HO-1 activity has been attributed by some to the HO-1-mediated increase in GSH and extracellular superoxide dismutase levels, and the decrease in iNOS [59,62,69]. The decrease in oxidative stress has been shown to counteract vasoconstrictors, including ET-1 and PE [18,24,25,62,69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The salutary effect of the enhancement of HO-1 activity has been attributed by some to the HO-1-mediated increase in GSH and extracellular superoxide dismutase levels, and the decrease in iNOS [59,62,69]. The decrease in oxidative stress has been shown to counteract vasoconstrictors, including ET-1 and PE [18,24,25,62,69].…”
Section: Discussionmentioning
confidence: 99%
“…These studies attribute the blood pressure lowering effect of HO-1 induction to various mechanisms, including decreased production of vasoconstrictor eicosanoids and increased production of CO [2,15,16]. CO has been shown to function as a vasodilator [17][18][19][20][21], a stimulator of soluble guanylate cyclase [22], an endogenous modulator of the cGMP signaling system [4], an activator of calciumactivated potassium channels (K Ca ) in vascular smooth muscle [23], and an inhibitor of endothelin-1 mediated vasoconstriction [18,24,25]. Recent reports have implicated HO in the regulation of renal salt excretion.…”
mentioning
confidence: 99%
“…IIIB1B and IVA2). Furthermore, inhibition of HO with chromium mesoporphyrin or treatment with HO-2 antisense oligodeoxynucleotides facilitated HPV in rat pulmonary arteries and intact animals (2189). Because this facilitation was prevented by ET-1 receptor blockade or removal of endothelium, it was concluded that CO suppressed ET-1 production and/or sensitivity (2189).…”
Section: Plasma Membranementioning
confidence: 99%
“…55). The blood pressure lowering effect of HO-1 can be attributed to various mechanisms, including decreased production of vasoconstrictor eicosanoids and increased production of CO, which functions as a vasodilator, a stimulator of soluble guanylate cyclase, an endogenous modulator of the cGMP signaling system, an activator of calcium-activated potassium channels in vascular smooth muscle, and an inhibitor of endothelin-1 (60,227). Acute elevation of renal perfusion pressure (RPP) induced a rise of CO and nitric oxide (NO) concentrations accompanied in the medullary tissue by natriuresis (108).…”
Section: Ho Isoform Expression In Kidneymentioning
confidence: 99%